A Social Network Analysis on Venture Capital Alliance's Exit from an Emerging Market. (28th June 2020) - Wu, Jing; Luo, Chuan; Liu, Ling
Abstract : This study investigated the impacts of network structure on a venture capital (VC) alliance's successful exit from an emerging market by empirically analyzing joint VC data in China. We find that, compared to a mature capital market, the mechanism not only has a certain commonality but also shows the emerging market's particularities. From the commonality perspective, the mechanism has a positive effect on successful exit by obtaining heterogeneity information. These particularities are manifested in the following three aspects. First, the mechanism is not conducive to deepening the enterprise value chain to establish credibility by obtaining short-term cash during an initial public offering with the enhancement of the VC alliance's intervention ability for enterprise development. In addition, a VC alliance's independent judgment is bound by the VC market. Furthermore, the problem of over-trust in investees reduces the likelihood of a VC alliance's successful exit. Therefore, we should pay more attention to the particularity of emerging markets such as China to improve the relevant management mechanism.